International multicenter cohort study on beta-blocker-free treatment strategies for catecholaminergic polymorphic ventricular tachycardia patients: ventricular tacchycardia - Neves, Raquel; Bains, Sahej; Bos, J. Martijn; van der Werf, Christian; Bergeman, Auke T.; Peltenburg, Puck; Blom, Nico A.; Sanatani, Shubhayan; Swan, Heikki; Probst, Vincent; Kannankeril, Prince J.; Skinner, Jonathan R.; et al. (JACC Clinical electrophysiology, 2025)
Background - Catecholaminergic polymorphic ventricular tachycardia (CPVT) is a rare, potentially life-threatening genetic heart disease. Nonselective beta-blockers (BBs) are highly effective in reducing CPVT-triggered arrhythmic events. However, some patients suffer from unacceptable BB side effects and might require strategies without a BB. - Objectives - This study sought to review the spectrum of and outcomes associated with BB-free treatment configurations in patients with CPVT enrolled in the International CPVT Registry. - Methods - From the Registry, patients with RYR2 variant-positive CPVT treated with a BB-free strategy for ≥6 months were included. Two treatment groups were defined: patients classified as very low risk and treated with intentional nontherapy (INT) and patients who needed to be treated but did not tolerate BBs and were treated with 3 different strategies. - Results - Overall, 100 of 1,017 patients (10%) were on a BB-free treatment strategy. There were 73 patients (33 females [42%]) in the INT group. In patients 66 (90%), INT was pursued after low-risk assessment in asymptomatic patients and absent or negligible stress test phenotype. Twenty-seven patients (22 females, 81%) were treated using 3 different BB-free treatment strategies (flecainide monotherapy, n = 21; left cardiac sympathetic denervation monotherapy, n = 2; flecainide + left cardiac sympathetic denervation, n = 4). In total, 25 patients (93%) were previously treated with BBs. During a median follow-up of 6 years (IQR: 3-9 years), 2 patients (2%) had a CPVT-associated event. - Conclusions - Although nonselective BBs remain the cornerstone treatment for CPVT, 10% of patients with CPVT required a BB-free treatment strategy. After careful risk assessment, safe and effective BB-free treatment strategies can be configured.
Online verfügbar: 18. Dezember 2024, Artikelversion: 24. Februar 2025
Gesehen am 17.07.2025